2017
DOI: 10.1007/s12275-017-6638-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression and enzymatic characterization of γ-glutamyltranspeptidase from Bacillus amyloliquefaciens

Abstract: SigmaB plays an important role in both osmoprotection and proper differentiation in Streptomyces coelicolor A3(2). We searched for candidate members of the sigmaB regulon from the genome database, using the consensus promoter sequence (GNNTN14-16GGGTAC/T). The list consists of 115 genes, and includes all the known sigmaB target genes and many other genes whose functions are related to stress protection and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Moreover, in addition to the regulatory genes mentioned above, many other genes regulated by SigB ( Lee et al, 2004b ) were also over-expressed in the Δ aor1 mutant compared to the wild-type. These included: catB ( SCO0666 ) ( Cho et al, 2000 ), coding for a catalase that was 11.4-fold up-regulated; trxC , coding for a thioredoxin C (4.7-fold); ssgC ( SCO7289 ) implied in differentiation (8.4-fold); 12 genes of an operon for gas vesicles proteins (GV) ( SCOs6496-6508; Figure 4 , coordinates 7189075-7199188), whose promoter is regulated by SigB and were more than 5-fold up-regulated (Supplementary Table S4 ); and another 15 genes, some of them with an unknown function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in addition to the regulatory genes mentioned above, many other genes regulated by SigB ( Lee et al, 2004b ) were also over-expressed in the Δ aor1 mutant compared to the wild-type. These included: catB ( SCO0666 ) ( Cho et al, 2000 ), coding for a catalase that was 11.4-fold up-regulated; trxC , coding for a thioredoxin C (4.7-fold); ssgC ( SCO7289 ) implied in differentiation (8.4-fold); 12 genes of an operon for gas vesicles proteins (GV) ( SCOs6496-6508; Figure 4 , coordinates 7189075-7199188), whose promoter is regulated by SigB and were more than 5-fold up-regulated (Supplementary Table S4 ); and another 15 genes, some of them with an unknown function.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the regulatory network and targets that respond to osmotic stress and heat shock mediated by the master sigma factor SigB, such as SigL, SigM, SigH, SigK, CatB, TrxC, SsgC and a whole gas vesicle (GV) operon ( Lee et al, 2004b , 2005 ; Facey et al, 2011 ), were found up-regulated in the S. coelicolor Δ aor1 mutant strain. The genes encoding WhiB ( SCO3034 ) (indirect target of SigB) and DpsA ( SCO0596 ) (direct target of SigH and SigB) were also differentially expressed and were up-regulated by 2.68-fold and 2.6-fold, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…TSSs of sig8 , dnaK1 , oxyR , trxA3 , sig22 , and opuBC1 were determined by 5′-RACE analysis of WT gene transcripts under stress conditions (Supplementary Figure S4), leading to the putative -35 and -10 promoter sequences shown in Figure 7 . Analysis of these promoter sequences using the PREDetector web-based program 1 revealed a consensus sequence BGVNVH-N 15 -GSNNHH ( Figure 7 ), which resembles that of σ B -specific promoters of S. coelicolor (GNNTN-N 14-16 -GGGTAY) (Y: C or T) (Lee et al, 2004b). …”
Section: Resultsmentioning
confidence: 99%
“…In S. coelicolor , σ B (Cho et al, 2001; Lee et al, 2004b) and σ K (Mao et al, 2009) are involved in regulation of ACT and RED biosynthesis, although the regulatory mechanisms are unclear. In Streptomyces chattanoogensis L10, alternative σ factor WhiG ch promotes natamycin biosynthesis by directly activating two structural genes, scnC and scnD (Liu S. P. et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Except for σ WhiG , S. coelicolor has nine other alternative σ factors (σ B , σ F , σ G , σ H , σ I , σ K , σ L , σ M , and σ N ), all belonging to the σ B -like σ factors, which are homologs of Bacillus subtilis σ B ( Cho et al, 2001 ; Lee et al, 2004 ). These σ B -like σ factors play important roles in the Streptomyces regulatory system ( Kelemen et al, 1996 ; Kormanec and Sevcikova, 2002 ; Lee et al, 2005 ; Mao et al, 2009 ; Wang et al, 2010 ).…”
Section: Group 3 σ Factorsmentioning
confidence: 99%